Analysis of a Steel Bridge Connected with Tunnel Considering Live Project Data Using SAP2000 - Dolly Dewangan; Shubham Dashore; Dr. S. K. Jaiswal (International Journal of Scientific Research in Civil Engineering, 2022)
Majority of the truss bridges in India and abroad are either structurally deficient and/or functionally obsolete. There is a desperate need to enhance the performance of these existing bridges by an appropriate technique which should be economical and with minimum disturbance to the traffic. The aim of the present analytical work is to know the effect of Pre-stressing on the member forces, deflections and total weight of steel of a statically determinate three types of trusses such as Pratt type or Warren truss..Pre-stressing technique has been adopted to upgrade the performance of the truss. The truss is pre-stressed with high tensile steel cable and the profile of the cable is straight. The truss is analysed for member forces and deflections using SAP 2000 Software. From the obtained analytical results, it is seen that there is a noticeable improvement in the performance of the structure. Member forces have been reduced significantly in the entire truss members and there is a reduction in deflection at the centre and material requirement after pre-stressing.
Keywords: Bridges; Truss; Pre-stressing; Cable; Member Forces; Deflections; SAP 2000